In-Vitro Activity of Silybin and Related Flavonolignans against Leishmania infantum and L. donovani - Olías-Molero, Ana Isabel; Jiménez-Antón, María Dolores; Biedermann, David; Corral, María J; Alunda, José María (Molecules (Basel, Switzerland), 2018)
Flavonolignans from the seeds of the milk thistle (Silybum marianum) have been extensively used in folk medicine for centuries. Confirmation of their properties as hepatoprotective, antioxidant and anticancer has been obtained using standardized extracts and purified flavonolignans. Information on their potential effect on Leishmania is very scarce. We have investigated the effect of silymarin, silybin and related flavonolignans on the multiplication of promastigotes in vitro and ex vivo on intracellular amastigotes of L. infantum (Li) and L. donovani (Ld), causative agents of human and canine visceral leishmaniasis (VL). In addition, the potential synergistic effect of the most active molecule and well-established antileishmanial drugs against promastigotes was explored. Dehydroisosilybin A elicited the highest inhibition against Ld and Li promastigotes with an approximate IC50 of 90.23 µM. This molecule showed a moderate synergism with amphotericin B (AmB) but not with SbIII or paromomycin, although it was ineffective against amastigotes. Antileishmanial activity on intracellular amastigotes of the two diastereoisomers of dehydrosilybin (10 µM) was comparable to that elicited by 0.1 µM AmB. Antiproliferative activity and safety of flavonolignans suggest the interest of exploring their potential value in combination therapy against VL.
Keywords: Leishmania donovani; Animals; Amphotericin B; SbIII; Antiprotozoal Agents; leishmanióza viscerální; Leishmania infantum; Leishmaniasis, Visceral; L. donovani; amphotericin; amfotericin B; paromomycin; lidé; antiprotozoální látky; dehydrosilybin; silybin; Dogs; silibinin; dehydroisosilybin; silymarin; Silybin; zvířata; leishmaniasis; psi; Silymarin; Humans